2010
DOI: 10.1038/hdy.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Inbred decorated crickets exhibit higher measures of macroparasitic immunity than outbred individuals

Abstract: Inbreeding is assumed to have negative effects on fitness, including the reduced ability to withstand immune challenges. We examined the immunological consequences of inbreeding in decorated crickets, Gryllodes sigillatus, by comparing lytic activity, phenoloxidase (PO) activity, and encapsulation ability of crickets from eight inbred lines with that of crickets from the outbred founder population. Surprisingly, crickets from inbred lines had a greater encapsulation ability compared with crickets from the outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 65 publications
6
33
1
Order By: Relevance
“…; Gershman et al. ). However, our analysis indicated that there was no effect of inbreeding on LRS, so there did not seem to be any net cost of inbreeding in this dataset.…”
Section: Discussionmentioning
confidence: 98%
“…; Gershman et al. ). However, our analysis indicated that there was no effect of inbreeding on LRS, so there did not seem to be any net cost of inbreeding in this dataset.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 21 studies that statistically tested for male and female differences in heritabilities, 12 found significant differences in a subset of the traits examined (Mousseau and Roff 1989;Wilcockson et al 1995;Ashman 1999Ashman , 2003Mignon-Grasteau 1999;Jensen et al 2003;Rolff et al 2005;Ng et al 2006;Fedorka et al 2007;Zillikens et al 2008;Gershman et al 2010;Stillwell and Davidowitz 2010).…”
Section: Characteristics Of the Datamentioning
confidence: 97%
“…Sexual dimorphism in immunoresponsiveness is widespread among invertebrate and vertebrate taxa (e.g., McKean and Nunney 2005;Love et al 2008;Nunn et al 2009;Gershman et al 2010;Aisenberg and Peretti 2011;Steiger et al 2011). In adult vertebrates, males typically respond to immunological challenges less robustly than females (Møller et al 1998;Klein 2000;Hasselquist 2007;Nunn et al 2009;Pap et al 2010; but see Tieleman et al 2010), but when this difference in immune function manifests itself is less well-documented, particularly in birds.…”
Section: Introductionmentioning
confidence: 97%